2013
DOI: 10.1103/physreve.87.042811
|View full text |Cite
|
Sign up to set email alerts
|

Emergent patterns of localized damage as a precursor to catastrophic failure in a random fuse network

Abstract: We study the failure of disordered materials by numerical simulations of the random fuse model. We identify emergent patterns of localized damage prior to catastrophic failure by statistically averaging the density of damage around the eventual failure nucleation point. The resulting pattern depends on fracture density and obeys the same scaling relations as would be expected for the stress field generated by a critical crack nucleating in a finite, disorder-free effective medium of varying size. The growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…We make the assumption that the characteristic extension of the fault zone controls failure in a similar manner as the length of a critical crack does in the context of fracture mechanics (for detailed discussion of this point see Ref. [13]). This allows us to relate the crack size to the number of AE events and to use the AE record for monitoring damage accumulation and predicting time-to-failure even when it is impossible to measure the crack size directly within an experiment.…”
Section: Introductionmentioning
confidence: 99%
“…We make the assumption that the characteristic extension of the fault zone controls failure in a similar manner as the length of a critical crack does in the context of fracture mechanics (for detailed discussion of this point see Ref. [13]). This allows us to relate the crack size to the number of AE events and to use the AE record for monitoring damage accumulation and predicting time-to-failure even when it is impossible to measure the crack size directly within an experiment.…”
Section: Introductionmentioning
confidence: 99%
“…This can be understood from the different failure modes of unconnected fiber bundles and of connected beam networks: For a connected network, lateral load redistribution leads to localized damage clusters, which form as weaker‐than‐average beams fail in a correlated manner and that extend in lateral direction. In studies of random fuse networks, such damage clusters were shown to control system strength in a manner very similar to small cracks that become critical at the failure stress . Thus, we observe that in a material with low disorder, cross linking may reduce strength even if it does not introduce damage, because cross links here facilitate the formation and lateral propagation of a critical crack which is impossible as long as the system consists of unconnected fibers.…”
Section: The Optimization Problemmentioning
confidence: 69%
“…In studies of random fuse networks, such damage clusters were shown to control system strength in a manner very similar to small cracks that become critical at the failure stress. [17,18] Thus, we observe that in a material with low disorder, cross linking may reduce strength even if it does not introduce damage, because cross links here facilitate the formation and lateral propagation of a critical crack which is impossible as long as the system consists of unconnected fibers. The effect is, of course, exacerbated if in addition the cross links are associated with damage (reduction in strength) of the load-carrying fibers.…”
Section: The Optimization Problemmentioning
confidence: 89%
See 2 more Smart Citations